Inclusive education: trends and perspectives - Quintero Ayala, Lyda Esperanza (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Inclusive education is understood as a process that proposes to recognize and respond to the diversity of needs presented by students so that their learning be able to effective, minimizing exclusion within and outside of Educational Institutions. This review article is the state of the art related to the project “Inclusive practices: a view from diversity”, which aims to recognize the practices and discourses of teachers in the Educational Institution of Boyacá about inclusive education. The investigations were classified by thematic organization of analysis, obtaining six sections that show the perspectives that are mobilized on the object of study. In each trend, significant results were found aimed at transforming teachers’ practices. The established categories were: inclusive education based on the legal framework, attitudes and perceptions of teachers, support networks and cooperative learning, promotion and alright inclusive pedagogical practices, inclusion issues, in terms of subjectivities - languages, and curricular proposal in the teacher training. in inclusive education.